Isomer-tagged differential-plunger measurements in proton-unbound 144Ho - Mason, P. J. R.; Cullen, D. M.; Scholey, C.; Dewald, A.; O. M√∂ller; H. Iwasaki; Pissulla, T.; Rother, W.; J.A. Dare; Greenlees, P. T.; Jakobsson, U.; Jones, P. M.; et al. (Physics Letters B, 2010)
The lifetime of an excited state above a weakly populated isomer in the proton-unbound odd‚Äìodd nucleus 144Ho has been measured using the recoil distance Doppler shift method. This measurement represents the first differential-plunger lifetime measurement to utilize recoil-isomer tagging. The first excited I œÄ = ( 10 + ) state above the two-quasiparticle œÄ h 11 / 2 ‚ä?ŒΩ h 11 / 2 ( 8 + ) isomer was determined to have a lifetime of œÑ = 6 ( 1 ) ¬† ps . Potential energy surface calculations, based on the configuration-constrained blocking method, predict the isomeric state to have Œ≥-soft triaxial-nuclear shape with | Œ≥ | ‚â?24 ¬∞ . The lifetime of the ( 10 + ) state can be understood from these calculations if there is a degree of rotational alignment in this band, with the K value being lower than the bandhead spin. However, the validity of the K quantum number with large predicted triaxiality and gamma softness requires further theoretical study.